From traitor to martyr: drawing lessons from the death and burial of Wang Jingwei, 1944 - Taylor, Jeremy E. (Cambridge University Press, 2018)
Based on recently re-opened files and publications in Nanjing, as well as published and newsreel accounts from the 1940s, this paper represents the first scholarly analysis of the rituals surrounding the death and burial of Wang Jingwei in Japanese-occupied China. Rather than locating this analysis purely in the literature on the history of the Second Sino-Japanese War (1937-1945), however, this paper asks what Wang Jingwei's Re-organized National Government might tell us about personality cults in the political culture of modern China. While Wang's burial was one which drew heavily on the precedent of Sun Yat-sen's funerals of the 1920s, it also presaged later spectacles of public mourning and post-mortem commemoration, such as Chiang Kai-shek's funeral in 1975 in Taipei. In focusing on this one specific event in the life of a "puppet government" then, this paper hopes to re-ignite scholarly interest in the study of "dead leaders" and their posthumous lives in modern Chinese history more generally.